Analysis of Cadmium (Cd) Heavy Metal Using the Atomic Abrsoption Spectrophotometry (AAS) Method in Canned Crab Products at Balai Pengujian Mutu Hasil Perikanan (BPMHP) Semarang, Central Java - Annisa Nur Rohmah Purnamasari; A Shofy Mubarak; Mulyono Mulyono (Universitas Airlangga, 2021)
Crab is fishery potential fishery product but it is a perishable food. Application and handling of crab can be done by processing it into canned products. Crab are very likely to be polluted by heavy metals in these waters because of heavy metal contamination is already very high in the ocean. The purpose of this activity is to find out directly assay methods of heavy cadmium (Cd) in canned crab product and know the standard limit of heavy metal cadmium (Cd) The analytical method of cadmium heavy metal content (Cd) on several canned crab products using the method analysis of SNI 2354.5: 2011. Based on the results of the crab product analytical (Portunus pelagicus) the results showed <0.5 mg / kg, so that based on the threshold of cadmium (Cd) on the tin crab pasteuriation product is regulated in SNI 6929: 2016, the product is safe and suitable for consumption.